2017
DOI: 10.5296/ijld.v7i1.11021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Learning Strategy on Undergraduate Nursing Students Enrolled in Nursing Administration Course

Abstract: Today's, higher education emphasizes the importance of student centered learning. Further the aim of nursing education should be on the process of thinking and involve being proactive, collaborative and quality oriented. Cooperative learning is an approach to the aim of student-centered activities towards the attainment of the outcomes-based environment as required by accrediting and certifying bodies and agencies of higher education. Cooperative learning most often involves small groups of students who contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Finally, the majority of students in another study supporting these findings reported that cooperative learning helped them in learning content of lesson and facilitated their communication while completing their group work. Cooperative learning was further considered as helping them to improve their grades [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the majority of students in another study supporting these findings reported that cooperative learning helped them in learning content of lesson and facilitated their communication while completing their group work. Cooperative learning was further considered as helping them to improve their grades [19].…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that the majority, 72% and 70% of students, reported that cooperative learning helped them to learn the lesson's content and facilitated for communicating respectively while completing their group work. A further 67% and 65% of the students considered cooperative learning as helping them to improve their grades, as learning activities were described as funny, and learning said to be better in a team setting [19].…”
Section: Perceptions Of Students and Teachers On Cooperative Learningmentioning
confidence: 99%
“…Online and o ine mixed teaching modes could provide the multi-spatial nature of teacher and student interaction. Teachers need to establish online teaching content platform, design how to teach method in online courses, and design o ine classroom teaching organization form and content [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research evidence suggests that the design of teaching links before, during and after class were the key content of online and o ine hybrid teaching design [20] . Group cooperative learning could be a teaching form of online and o ine teaching mode, which can effectively promote students' learning interaction and knowledge exchange [21] .…”
Section: Introductionmentioning
confidence: 99%
“…습결과를 나누면서 서로에게 배우는 기회를 가질 수 있고, 서 로 돕는 가운데 학습과제를 해결하게 되어 학업성취도, 자기주 도적 학습능력 및 협동심 향상에도 긍정적인 효과가 있는 것 으로 보고하고 있다 (Lee, 2017;Yoon & Kim, 2001). 그동안 국내외 간호 교육에서 직소모형을 적용한 연구를 살펴보면 정 상분만, 감염, 의사소통, 기본간호학 수업 내용 등을 주제로 직 소학습을 시행하였으며 이를 통해 간호 지식과 관련 주제에 대한 인식 및 학습만족도가 향상되었고 (Cho, 2015;Sumitra, Frincy, Reena, Mariya, & Shilpa, 2017) (Eon & Shin, 2017;Mahmoud, 2017;Nayereh, Hamid, & Koresh, 2011;Park, 2010…”
unclassified